Dual secretion locations on type II cells in the avian lung suggest local as well as general roles of surfactant. (3rd May 2016) - Bódi, Ildikó; Kocsis, Katalin; Benyeda, Zsófia; Fejszák, Nóra; Molnár, Dávid; Nagy, Nándor; Oláh, Imre
ABSTRACT: Transmission electron microscopy indicates that the avian lung surfactant may be secreted in two directions: a) into air passages of parabronchus, atrium and infundibulum where it forms a trilaminar substance serving the respiratory role and b) to the basolateral surface—intercellular space—of type II pneumocytes, contributing to the innate and adoptive immune responses of lung. Basolateral secretion may be confirmed by the presence of trilaminal substance in the intercellular space of type II pneumocytes. Fusion of surfactant containing vesicles with the lateral plasma membrane may result in membrane fusion of neighboring cells and subsequently formation of multinucleated giant cell. The indistinct and in some places discontinuous basal lamina in the parabronchial atrium and infundibulum permits the hydrophilic surfactant proteins to spread into the interstitium of air‐blood capillary region. The hydrophilic surfactant proteins may activate lung interstitial macrophages to migrate into the air passages where they appear as "free avian respiratory macrophages." Therefore, in the interstitium the hydrophilic surfactant proteins are essential soluble components of innate immunity. J. Morphol. 277:1062–1071, 2016. © 2016 Wiley Periodicals, Inc.